2015
DOI: 10.1111/jch.12534
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Short‐Term Blood Pressure Variability and Subclinical Renal Damage in Essential Hypertensive Patients

Abstract: The authors aimed to analyze the relationship between subclinical renal damage, defined as the presence of microalbuminuria or an estimated glomerular filtration rate (eGFR) between 30 mL/min/1.73 m 2 and 60 mL/min/ 1.73 m 2 and short-term blood pressure (BP) variability, assessed as average real variability (ARV), weighted standard deviation (SD) of 24-hour BP, and SD of daytime and nighttime BP. A total of 328 hypertensive patients underwent 24-hour ambulatory BP monitoring, 24-hour albumin excretion rate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…The 24-h rate of SBP variation was shown to be a strong predictor of impaired renal function (OR per 0.1 mmHg/min increase, 1.49 [1.18–1.88]; p=0.001) [20]. Similar results were reported when linking other parameters of short-term BP variability (ARV of 24-hours SBP, weighted SD of 24-hours SBP) with eGFR in patients with microalbuminuria [7]. To the best of our knowledge, all the studies on BP variability and renal function were conducted in hypertensive patients; and data of critically ill patients, whose renal function was often impaired, was scarce.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The 24-h rate of SBP variation was shown to be a strong predictor of impaired renal function (OR per 0.1 mmHg/min increase, 1.49 [1.18–1.88]; p=0.001) [20]. Similar results were reported when linking other parameters of short-term BP variability (ARV of 24-hours SBP, weighted SD of 24-hours SBP) with eGFR in patients with microalbuminuria [7]. To the best of our knowledge, all the studies on BP variability and renal function were conducted in hypertensive patients; and data of critically ill patients, whose renal function was often impaired, was scarce.…”
Section: Discussionsupporting
confidence: 71%
“…An association between increased short-term BP variability and subclinical renal damage, which includes the presence of microalbuminuria or decrease of estimated glomerular filtration rate (eGFR), has been observed in essential hypertensive patients [7]. Kidney hypoxia or ischemia-reperfusion injury is thought to occur during the course of BP fluctuations,[8] which could occasionally develop into acute kidney injury (AKI), particularly in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have a shorter duration of follow‐up (3–4 years duration), which may not be able to show the effect of BPV on renal function decline. Other studies that examined short‐term 24‐hour BPV also showed that BPV was associated with decline in renal function, suggesting that both short‐ and long‐term BPV are important in determining the progression of kidney function deterioration in patients with hypertension …”
Section: Discussionmentioning
confidence: 98%
“…The additional important factor is how obesity parameters variability during the long period (several years) influences the BPV, because prolonged obesity leads to development of uncontrolled blood pressures and cardiovascular complications (8,32,33).…”
Section: Discussionmentioning
confidence: 99%